Mean Platelet Volume, Vitamin D and C Reactive Protein Levels in Normal Weight Children with Primary Snoring and Obstructive Sleep Apnea Syndrome. - Anna Maria Zicari; Francesca Occasi; Federica Di Mauro; Valeria Lollobrigida; Marco Di Fraia; Vincenzo Savastano; Lorenzo Loffredo; Francesco Nicita; Alberto Spalice; Marzia Duse (PLoS ONE, 2016)
INTRODUCTION:Studies on Mean Platelet Volume (MPV) in children with Sleep Disordered Breathing (SDB) report conflicting results and the hypothesis of an intermittent hypoxemia leading to a systemic inflammation is reaching consensus. Vitamin D exerts anti-inflammatory properties and its deficiency has been supposed to play a role in sleep disorders. Emerging interest is rising about Primary Snoring (PS) since it is reasonable that also undetectable alteration of hypoxia might predispose to an increased production of inflammatory mediators. In this perspective, in a group of children affected by SDB, our aim was to investigate MPV, vitamin D and C Reactive Protein (CRP) levels, which had been previously evaluated separately in different studies focused only on Obstructive Sleep Apnea Syndrome (OSAS). MATERIALS AND METHODS:We enrolled 137 children: 70 healthy controls (HC), 67 affected by SDB undergoing a polysomnographic evaluation, 22 with a diagnosis of PS and 45 with a diagnosis of OSAS. All patients underwent routine biochemical evaluations including blood cell counts, CRP and vitamin D. RESULTS:Children affected by SDB had a mean age of 8.49±2.19 and were prevalently males (23 females, 34%; 44 males, 66%). MPV levels were higher in OSAS and PS when compared to HC; platelet count (PLT) and CRP levels were higher while Vitamin D levels were lower in children with SDB when compared to HC. MPV levels were correlated with PLT (r = -0.54; p<0.001), vitamin D (r = -0.39; p<0.001) and CRP (r = 0.21; p<0.01). A multiple regression was run to predict MPV levels from vitamin D, CRP and PLT and these variables significantly predicted MPV (F = 17.42, p<0.0001; adjusted R2 = 0.37). Only platelet count and vitamin D added statistically significantly to the prediction (p<0.05). CONCLUSION:The present study provides evidence of higher MPV and lower vitamin D levels in children with PS as well as in children with OSAS, and supports the underlying inflammation, hence, highlighting the importance of an early diagnosis of this previously considered benign form of SDB.